Acrylate formation from CO2 and ethylene mediated by nickel complexes: A theoretical study - Pleßow, Philipp; Hofmann, Peter (Organometallics, 2014)
The first step of the nickel-mediated synthesis of acrylates from carbon dioxide (CO2) and ethylene is the formation of nickelalactones. Nickelalactones could then react to give complexes containing acrylic acid moieties. Such a spontaneous reaction, however, is usually not observed and most progress has recently been made by cleaving the lactones with auxiliaries such as Lewis acids and strong bases. Here we investigate in detail the coupling of CO2 and ethylene and further reactivity in absence of auxiliaries mediated by nickel complexes bearing bidentate ligands. We have found a new mechanism for lactone formation which, for some bidentate ligands, is favored over the mechanism described in the literature. Furthermore, we found that β-H elimination leading to ring contraction of the lactone is almost feasible at room temperature. Importantly, however, all investigated mechanisms for formation of acrylic acid complexes require higher activation free energies of ca. 130 kJ/mol and are not accessible at ambient or slightly elevated temperatures.